2011
DOI: 10.1080/09540121.2010.498909
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact of a community-based adherence support programme on ART outcomes in selected government HIV treatment sites in South Africa

Abstract: This study assessed the impact of a community-based adherence support service on the outcomes of patients on antiretroviral therapy (ART). The evaluation was a retrospective study based on patient clinical records. This study noted that a significantly higher proportion of patients with a community-based adherence supporter (also known as a patient advocate, PA) had viral load (VL) of less than 400 copies/ml at six months of treatment (70%, p=0.001); a significantly higher proportion of patients with PAs (89%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
2
58
0
1
Order By: Relevance
“…The assistance of the health worker in disclosing their status will help improving their confidence and lessening the myths around HIV and ART (Igumbor et al, 2011;Chang et al, 2010;Kipp et al, 2012 andZachariah et al, 2007). Mwai et al, (2013) finds that material and service supports in the form of food, medicine, condom distribution, ART and cotrimoxale deliveries, laboratories samples management, accompaniment to the clinic, registering, measuring and checking vital signs, RT effect monitoring, HIV development monitoring, personal care in cleaning wounds and getting dressed, training and jobs support amd screening is very much needed by PLWHA.…”
Section: The Effect Of Family Supportmentioning
confidence: 99%
“…The assistance of the health worker in disclosing their status will help improving their confidence and lessening the myths around HIV and ART (Igumbor et al, 2011;Chang et al, 2010;Kipp et al, 2012 andZachariah et al, 2007). Mwai et al, (2013) finds that material and service supports in the form of food, medicine, condom distribution, ART and cotrimoxale deliveries, laboratories samples management, accompaniment to the clinic, registering, measuring and checking vital signs, RT effect monitoring, HIV development monitoring, personal care in cleaning wounds and getting dressed, training and jobs support amd screening is very much needed by PLWHA.…”
Section: The Effect Of Family Supportmentioning
confidence: 99%
“…The same intervention decreased virologic failure rates at and after 96 weeks into ART (Chang et al 2010). Positive benefits on retention in HIV care were also reported in quasi-experimental studies of CHW use in Zambia (Torpey et al 2008), South Africa (Igumbor et al 2011) and Malawi (Zachariah et al 2007). …”
Section: Theory Of Changementioning
confidence: 65%
“…In the South African study, ART patients with CHW adherence support had higher treatment pick-up rates (95% versus 67%, p = 0.02) and were more likely to have a suppressed viral load after six months of treatment (70% versus 30%, p < 0.01) (Igumbor et al 2011). In addition, a home-based HIV care strategy in Uganda using lay health workers was found to be as effective as a clinic-based strategy on viral suppression after six months of ART (Jaffar et al 2009).…”
Section: Theory Of Changementioning
confidence: 99%
“…This often comprises nonclinical, community-based services such as, but not limited to, spiritual, legal and economic support. While psychological care and support can come from staff at the health facility treating the patient, several studies have demonstrated that support is more effective when coming from a focused, on-going program in the community where the patient resides [6]- [9].…”
Section: Introductionmentioning
confidence: 99%